Microglia-Derived NLRP3 Activation Mediates the Pressor Effect of Prorenin in the Rostral Ventrolateral Medulla of Stress-Induced Hypertensive Rats - Li Hu; Shutian Zhang; Kokwin Ooi; Xuehai Wu; Jiaxiang Wu; Jian Cai; Yinggang Sun; Jijiang Wang; Danian Zhu; Fuxue Chen; Chunmei Xia (Neuroscience Bulletin, 2020)
Increased microglial activation and neuroinflammation within autonomic brain regions such as the rostral ventrolateral medulla (RVLM) have been implicated in stress-induced hypertension (SIH). Prorenin, a member of the brain renin-angiotensin system (RAS), can directly activate microglia. The present study aimed to investigate the effects of prorenin on microglial activation in the RVLM of SIH rats. Rats were subjected to intermittent electric foot-shocks plus noise, this stress was administered for 2 h twice daily for 15 consecutive days, and mean arterial pressure (MAP) and renal sympathetic nerve activity (RSNA) were monitored. The results showed that MAP and RSNA were augmented, and this paralleled increased pro-inflammatory phenotype (M1) switching. Prorenin and its receptor (PRR) expression and the NLR family pyrin domain containing 3 (NLRP3) activation were increased in RVLM of SIH rats. In addition, PLX5622 (a microglial depletion agent), MCC950 (a NLRP3 inhibitor), and/or PRO20 (a (Pro)renin receptor antagonist) had antihypertensive effects in the rats. The NLRP3 expression in the RVLM was decreased in SIH rats treated with PLX5622. Mito-tracker staining showed translocation of NLRP3 from mitochondria to the cytoplasm in prorenin-stimulated microglia. Prorenin increased the ROS-triggering M1 phenotype-switching and NLRP3 activation, while MCC950 decreased the M1 polarization. In conclusion, upregulated prorenin in the RVLM may be involved in the pathogenesis of SIH, mediated by activation of the microglia-derived NLRP3 inflammasome. The link between prorenin and NLRP3 in microglia provides insights for the treatment of stress-related hypertension.